A Look into the AP Statistics Classroom: Who Teaches It and What Aspects of Statistics Do They Emphasize?. Issue 1 (2nd January 2022) - Lee, Hollylynne S.; Vaskalis, Zachary T.; Stokes, David J.; Harrison, Taylor R.
Abstract : With Advanced Placement (AP) Statistics continuing to grow in enrollment and its importance as an optional course in high school, we aimed to understand more about the practices in this course. From a survey of 445 AP Statistics teachers, and interviews with 18 volunteers, we offer insight into the teachers of this course, what their classrooms look like, and the aspects of statistics that are emphasized in their curriculum and instruction. Results can assist those in the statistics education community who work with AP Statistics teachers on a local, regional, or national level.